(untitled) (Heritage, 2021)
When it comes to conducting monetary policy in the Republic of Serbia, it is necessary to emphasize that the basic framework for regulating the mentioned policy was adopted and the Law on the National Bank of Serbia was adopted. The author of this paper emphasizes the need to respect the required primary goal of the National Bank of Serbia, i.e. it is necessary to respect the achievement and maintenance of price stability, which contributes to preserving the stability of the financial system and sustainable economic growth of the Serbian economy as a whole. There are numerous ways of influencing the National Bank of the Republic of Serbia on the realization of monetary policy, but in this paper the author emphasizes only some of the most important ones: achieving price stability, implementation of the inflation targeting regime by the National Bank of Serbia and others. In addition, in order to achieve a sound monetary policy, it is necessary to make an expression in a given interval through the disclosed annual consumer price indices, as well as with the recommended expression of the estimated allowed deviation. In order to complete the monetary policy, it is possible to apply a realistic representation of the reference interest rate. It is the basic instrument of monetary policy in the inflation targeting regime that the National Bank seeks to maintain at a real level in a given observation period. In addition, the National Bank, through other monetary instruments, creates the overall conditions in which monetary policy instruments will operate, such as interventions in the foreign exchange market, conducting open market operations, prescribing required reserves, providing credit and deposit facilities and performing continuous interventions in the foreign exchange market Republic of Serbia. In this paper, the author emphasizes the existence of some other significant conditions of influence on the conduct of general monetary policy in the economy of the Republic of Serbia. The author of the paper emphasized the importance of the implementation of real estate appraisal of legal entities in the Republic of Serbia, as well as the importance of forming a database of appraised real estate by licensed appraisers.